The professional [videorecording (Blu-Ray)] - Reno, Jean, 1948-; Oldman, Gary; Portman, Natalie, 1981-; Aiello, Danny, 1933-2019; Besson, Luc; Besson, Luc; Serra, Eric (Columbia TriStar Home Video, 2009)
New York's top hit man becomes the unwilling guardian of his next-door neighbors' 12-year-old daughter and helps her track the psychotic agent who murdered her family so she can exact her revenge.